Indonesia's Economic Conditions During The Covid-19 Pandemic And Improving The Economy Post-Pandemi (Pena Cendekia Insani, 2022)
This observes the interests of determining the improvements and projections of the Indonesian financial system from 2014 to 2020 after the Corona Pandemic. This study is a qualitative study with a descriptive evaluation method with the aim of studying and imparting an overview of the condition of the Indonesian economic device. based totally on research completed with the aid of the use of global establishments and national establishments, it is estimated that Indonesia's financial increase in 2020 will experience a slowdown unlike in previous years. based on the IMF Indonesia's monetary boom in 2020 amounted to 0.5%, in assessment to an evaluation conducted thru the area of financial institutions and ADB, every of which estimates Indonesia's economic growth to be 2.5% and five.2%. any other is primarily based mostly on projections made with the resources of Bappenas that the Indonesian monetary gadget can still develop inside the variety of 0.4-2.3% in 2020. There are many problems that especially the economic Indonesian economy has really plummeted, economic conditions in Indonesia look very poor, globally 2020 is estimated, due to this condition triggering a decline in trade in Indonesia and even international trade. The pandemic has succeeded in making the Indonesian economy shaken. All indicators covering macroeconomic conditions, ranging from economic growth, household consumption, inflation, unemployment, poverty rate, to manufacturing Purchasing Managers Index (PMI) plummeted. And there are many more losses that have occurred as a result of covid-19, not a few also employees or workers who were laid off and lost their jobs so the unemployment rate in Indonesia is increasing and there are fewer sources of income because there are many companies and even shops are closed and even bankrupt.